Ureteric double-J stent related complications: a single tertiary care center experience from South India - Gurram, Maliikarjuna; G., Ravichander; Jagirdhar, Ravi; Chandra, Praveen (International Journal of Research in Medical Sciences, 2018)
Background: The double-J (DJ) ureteral stents is most commonly used urological procedure and is associated with complications. This study was done to analyse the complications of ureteral DJ stents, modalities of management and outcomes. Methods: The present study is a prospective observational study of patients who presented with DJ stent related complications between February 2016 and November 2017. Patients were evaluated by history, examination, urine analysis, cultures, KUB ultrasonography, abdominal roentgenogram, CT-KUB, intravenous urogram and DTPA renogram. Complications like fever, hematuria and irritable bladder symptoms were managed conservatively. Patients with stent migration underwent endoscopic removal. Combined endourological procedures were performed in single or staged manner in cases with retained DJS with encrustation. Results: Total 120 patients presented with DJ stent complications during the study period. Males were 63.3% and females 36.7%. The mean age was 31.5 years. The majority 65.33% of the stents were placed for postsurgical prophylaxis. Irritable bladder symptoms 42.5% was most common complication, followed by retained stent with encrustation 17.5%, fever 15.9%, hematuria 13.3%, stent migration 5.8% and retained sent with minimal and no encrustation 5%. Stent removal was done in 47 (39.16%) patients; all patients with retained stent, stent migration, 5 (26.3%) patients with fever and 8 (15.6%) patients with irritable bladder symptoms. Common site of encrustation was bladder alone and kidney with bladder in 5 (23.80%) patients each. The mean stent indwelling time was 3.2 years. Twenty-one (17.5%) patients required combined endourological procedures such as cystolithotripsy (CLT), ureteroscopic lithotripsy (URSL), percutaneous nephrolithotomy (PCNL) with intracorporal lithotripsy. One (4.76%) patient required nephrectomy. Conclusions: Double-J stent is an important tool to prevent and relieve obstruction. Their use must be strictly restricted to selected cases with proper documentation, counseling and close tracking. Encrustation in forgotten stents should be managed with stent removal with combined endourologic techniques.